Analysis Of Entrepreneurship Character in Micro, Small and Medium Enterprises (MSMEs) In Alun-Alun Lampa, Mapilli District - Awaru, A. Octamaya Tenri (Universitas Negeri Makassar, 2023)
Entrepreneurial character is important to determine the level of business success. Knowing the different behavior patterns possessed by entrepreneurs, will help entrepreneurs to learn and develop. The purpose of this study was to determine the entrepreneurial character possessed by Micro, Small and Medium Enterprises in running a business in the Lampa square, Mapilli sub-district. This research is a quantitative descriptive research. Respondents were selected using a saturated sampling technique with a total population of 33 people. The data collection technique used was distributing questionnaires to respondents. The results of the angket questionnaire were analyzed by interpreting the score of the questionnaire according to Sugiyono. The results of the study show that the entrepreneurial character possessed by Micro Business actors, Small and Medium Enterprises in the Lampa square, Mapilli District, with an average score of 83.56% in the very high category. The percentages for each indicator are (1) 94.5% confident, (2) 93.3% task and result oriented, (3) 89.1% honest, (4) 86.7% future oriented, ( 5) Creative 84.8%, (6) Leadership 76.9%, (7) Dare to take risks 75.7%, and (8) innovation 67.3%. So it can be concluded that the entrepreneurial character that dominates MSME players in Lampa Square is self-confidence and the weakest character is innovation. (7) Dare to take risks 75.7%, and (8) innovation 67.3%. So it can be concluded that the entrepreneurial character that dominates MSME players in Lampa Square is self-confidence and the weakest character is innovation. (7) Dare to take risks 75.7%, and (8) innovation 67.3%. So it can be concluded that the entrepreneurial character that dominates MSME players in Lampa Square is self-confidence and the weakest character is innovation.